Ornamental Barberry Twigs as an Underexploited Source of Berberine-Rich Extracts—Preliminary Research - Michał Miłek; Małgorzata Dżugan; Natalia Pieńkowska; Sabina Galiniak; Mateusz Mołoń; Wojciech Litwińczuk (Current Issues in Molecular Biology)
Berberine is a natural substance obtained from the roots of common barberry which, due to its strong pharmacological activity, is a commonly tested ingredient of dietary supplements. However, ornamental barberries, which are widely available, have not been considered as a source of berberine so far. The research aimed to check whether the ornamental barberry leaves and twigs could be used as an easily accessible raw material for obtaining natural berberine-rich extract with biological activity. Twigs and leaves of seven cultivars of ornamental barberry extracts were assessed for their polyphenol content, antioxidant potential (FRAP and DPPH), and berberine content using high-performance thin layer chromatography (HPTLC). As a reference, commercially available roots of Berberis vulgaris were used. For the next step, selected extracts (two with high and two with low berberine content) were tested on three cell lines (HaCaT, A375, Caco-2) using neutral red assay, and pure berberine sulfate (1–100 μg mL−1) was used as a control. Although the antioxidant potential of aqueous–methanol extracts of tested barberry was higher for the leaves than for the twigs, the berberine content was determined only in the twig extracts (from 42 to 676 mg 100 g−1). Studies on cell lines have shown the general toxicity of barberry extracts, but the observed effect was not directly correlated with the content of the alkaloid. However, the extract showed greater activity compared to an analogous dose of pure berberine, suggesting a significant effect of the matrix composition. For the first time, it was shown that the twigs of selected cultivars of ornamental barberry can be considered as a promising berberine source for the pharmaceutical industry to develop new effective formulations. However, these findings require further studies.